2009
DOI: 10.3151/jact.7.229
|View full text |Cite
|
Sign up to set email alerts
|

Biaxial Fracture Behaviour of Steel-Span and Steel-Fibre- Reinforced Concrete

Abstract: The wedge splitting method according Tschegg has been used to determine the fracture-mechanical values for cubes (e.g. 150 x 150 x 150 mm 3 ) under uniaxial (tension) and biaxial (compression + orthogonal tension) loading. The steelfibre-reinforced concrete had fibre lengths of 15 to 60 mm and a volume content of 0.5 to 1%. The fracture behaviour and the influence of the fibre length and the fibre content on the fracture parameters can be explained qualitatively using a very simple model. Finally, some aspects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 17 publications
0
9
1
1
Order By: Relevance
“…Tschegg et al [9] and Elser [10] investigated fracture mechanical properties of different concretes and cement bonded materials under biaxial tensile-compression load and found out that the notch tensile strength and the fracture energy decreases with the application of an additional compression load perpendicular to the acting tensile load. Subsequently, Elser et al [11] and Tschegg [12] investigated different steel and polypropylene fibre reinforced concretes, where a similar decrease of the fracture energy has been observed.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…Tschegg et al [9] and Elser [10] investigated fracture mechanical properties of different concretes and cement bonded materials under biaxial tensile-compression load and found out that the notch tensile strength and the fracture energy decreases with the application of an additional compression load perpendicular to the acting tensile load. Subsequently, Elser et al [11] and Tschegg [12] investigated different steel and polypropylene fibre reinforced concretes, where a similar decrease of the fracture energy has been observed.…”
Section: Introductionmentioning
confidence: 85%
“…In previous work, Elser [10], Elser et al [11] and Tschegg [12] reported that the specific dissipated energy of FRC, as a function of the compressive stress ratio, was of a ''wave-like'' shape, but this phenomenon has not been explained as of now. In the work of Elser [10] and Tschegg [12] concrete specimens reinforced with steel fibres of length 60 mm and 30 mm have been studied.…”
Section: Reasons For the Decrease Of The Dissipated Energy Under Biaxmentioning
confidence: 93%
See 2 more Smart Citations
“…O erro de medição devido ao atrito entre as peças de transmissão e a cunha é minimizado pelos rolamentos que compõem o equipamento de ensaio e, por isso, é insignificante (menor que 1%). Já a força de divisão (F H ) pode ser determinada por meio de um cálculo simples e a força vertical (F V ) é baixa e não perturba o comportamento da fratura (TSCHEGG, 2009;TSCHEGG;ELSER;STANZL-TSCHEGG, 1995a).…”
Section: Método Aenor Une 83515: 2010unclassified